DO SUSTAINABILITY AND COVID-19 AFFECT FIRMS PERFORMANCE, VALUE AND RISK IN BRAZIL? - De Oliveira, Thaissa; Jesuka, Duterval; Peixoto, Fernanda Maciel; Tizziotti, Catarine Palmieri Pitangui (Advances in Scientific and Applied Accounting, 2021)
Objective: This study investigated the impacts of the B3 sustainability index and the Covid-19 pandemic on the value, performance, and risk of 494 Brazilian listed firms from 2010 to 2020. Method: The difference-in-difference regression method was adopted to observe the difference in performance, value, and risk variation between listed and non-listed companies on the ISE. The following dependent variables were selected: Return on Assets, Return on Equity, Price-To-Book Value, Market-to-book, Volatility and Beta. To measure sustainability, the B3 ISE (Corporate Sustainability Index) was adopted and the effect of the Covid-19 pandemic in 2020 was considered. Results: The main results show that adherence to the B3 corporate sustainability index significantly reduces Return on Assets, Return on Equity, Price-To-Book Value, Market-to-Book, Beta and Corporate Volatility of Brazilian companies. No significant differences were found in the variation of performance, value and risk between the ISE listed firms and their counterparts. Evidence shows that in 2020 there was a reduction in the value, performance the volatility of Brazilian companies, influenced by the emergence and expansion of Covid-19. Contributions: The study provided evidence that the sustainable practices of the ISE listed companies positively influence market value and reduce investor risk perception. In addition, the study innovates by presenting empirical evidence on the implications of Covid-19 on the value, performance and risk of Brazilian companies.